(untitled) - Dobrotkova, Marta (Doprava a spoje, 2011)
In determining the unit price should be based on several factors, such as on the basis of costs incurred to implement services. Competition is one of these factors. At present, competition gives the definition of the price interval. On that basis, the company may to determine a price that would serves to determine an indicative amount of actual prices by using correlation and regression analysis,. It is important to realize that not every transportation has to be profitable, but profit would have been achieved in the long term.